1983
DOI: 10.1093/infdis/147.3.406
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Human T-Cell Leukemia/Lymphoma Virus

Abstract: Human T (thymus-derived)-cell leukemia/lymphoma virus (HTLV) is the first retrovirus consistently isolated from humans. Seroepidemiologic testing for antibodies to HTLV document the following. (1) HTLV is associated with a spectrum of mature T-cell lymphoreticular neoplasms. (2) HTLV is strongly associated with clusters of adult T-cell leukemia in Japan and a related syndrome, lymphosarcoma T-cell leukemia in the Caribbean. (3) Virus-positive infections from other areas of the world share similar clinicopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(43 citation statements)
references
References 28 publications
0
41
0
2
Order By: Relevance
“…Since the discovery of HTLV-I, many seroepidemiologic studies of this new retrovirus have been carried out in several areas of the world (2,6,18). These studies have shown that the most endemic areas in the world were the southwestern part of Japan-Kyushu Island and the Ryukyu Archipelago including Okinawa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of HTLV-I, many seroepidemiologic studies of this new retrovirus have been carried out in several areas of the world (2,6,18). These studies have shown that the most endemic areas in the world were the southwestern part of Japan-Kyushu Island and the Ryukyu Archipelago including Okinawa.…”
Section: Discussionmentioning
confidence: 99%
“…The seroepidemiologic study of HTLV-I in the endemic areas of All (2,6) shows that there are many individuals positive for antibody to HTLV-I (anti-HTLV-I), who are regarded as carriers of' HTLV-I (3). The age-and sexspecific distribution of anti-HTLV-I positive individuals shows certain characteristic features (8,18).…”
mentioning
confidence: 99%
“…Uchiyama et al (46) had described a high-grade T cell malignancy, adult T cell leukemia/lymphoma (ATLL), which was endemic in southwestern Japan. A viral etiology was suspected, and subsequently, Gallo and colleagues (47) (48,49). The pathological spectrum of ATLL was broad, but both serological studies for antibodies to the virus and molecular detection of viral sequences facilitated diagnosis (50).…”
Section: The New Technologiesmentioning
confidence: 99%
“…Surveys have reported the following high prevalences among adults in these areas of Japan: Nagasaki, 37%; Kagoshima, 24%; and Okinawa, between 10% and 51%. [5][6][7] Hawaiian-Japanese emigrants from Table). For this survey, specific identifier information (i.e., name and Social Security number) were unlinked from the specimen in order to ensure confidentiality.…”
Section: Introductionmentioning
confidence: 99%